How has the illegal wildlife trade evolved in Tolima? Multitemporal analysis of a threat to biodiversity (2024)
The illegal trade of species is a highly lucrative criminal activity that threatens the survival of numerous species. The department of Tolima, located in central Colombia, is considered a hotspot for these activities due to its rich biodiversity and strategic location. To understand the behavior of illegal wildlife trade in this department, we analyzed the number of seizure reports and voluntary deliveries between 2013 and 2022 using the information provided by the Regional Autonomous Corporation of Tolima (Cortolima): 4067 individuals were recorded belonging to 218 species, 150 genera, 96 families, and 45 orders. Birds were the most trafficked group (56.2%), followed by reptiles (34.25%) and mammals (6.68%). The most affected species included the Morroccoy tortoise (Chelonoidis carbonarius), the common parrot (A. ochrocephala), and the tan parakeet (B. jugularis); 9.17% of these species are threatened at the international level and 8.25% at the national level, while 35.32% are listed in the CITES appendices. The years 2021 (21.63%) and 2016 (18.28%) stood out for significant seizures, while 2013 (33.91%), 2014 (29.32%), and 2015 (24.54%) recorded the highest number of species deliveries to Cortolima. The central zone of the department was the most representative throughout the period studied (66.24%). These findings provide a detailed and updated view of illegal species trafficking in Tolima, essential in designing and implementing conservation and protection measures for endangered species.